Awareness and Perception Regarding Health Insurance among Community people in a Municipality: A Cross Sectional Study (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Health insurance program is a social protection program of the government of Nepal, which aims to enable its citizens to have access to quality health care services without placing financial burden on them. There was insufficient knowledge and awareness of the health insurance activities. Insured persons have complained of poor attitude and behaviour of service providers operating in the health insurance scheme. The aim of this study was to investigate the awareness and perception regarding health insurance among community people in a municipality.MATERIALS AND METHODS: A cross-sectional survey assessing awareness and perception of community people on health insurance was conducted using a structured questionnaire in Bardibas municipality of Mahottari district of Nepal during the month of August 2019 to October 2019. A total of 422 sample were selected by use of simple random sampling technique and face-to-face interview was conducted using the structured questionnaire. Multivariable logistic regression model was applied to test the effects of independent variables after adjusted potential confounders. A p-value ≤ 0.05 was considered statistically significant.RESULTS: Participants who were from age group of less than 30 years [aOR 2.82; 95% CI (1.46-5.47)] of male gender [aOR 2.03; 95% CI (1.13-3.66)], from upper caste [aOR 6.22; 95% CI (2.97-13.0)], and had higher secondary education level and above [aOR 4.66; 95% CI (2.81-7.74)] were likely to have adequate level of awareness than counterparts. Likewise, participants who were married [aOR 3.46; 95% CI (1.57- 7.63)], had higher secondary education level and above [aOR 4.74; 95% CI (2.85- 7.87)], and involved in services or business [aOR 8.67; 95% CI (3.54-21.23)], were more likely to have satisfactory perception on health insurance.CONCLUSIONS: Education level and occupation has influence on the level of awareness and perception of health insurance. Therefore, awareness programme on health insurance need to be implemented through mass media campaign.